2022
DOI: 10.3390/microorganisms10091738
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility for Thromboembolic Events versus High Bleeding Risk Associated with COVID-19

Abstract: The infection with the SARS-CoV-2 virus is associated with numerous systemic involvements. Besides the severe respiratory injuries and cardiovascular complications, it became obvious early on that this disease carries an increased risk of thromboembolic events, but a higher propensity for bleedings as well. We researched the medical literature over significant PubMed published articles debating on the prevalence, category of patients, the moment of occurrence, and evolution of venous thromboembolism (VTE), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…It is also important emphasizing that there are some pathophysiological explanations indicating that patients who develop AF de novo during pneumonia have increased risk of bleeding events (depletion of coagulation factors and platelets as a result of inflammatory response during infection) ( 53 ). Based on the available data, it can be conservatively assumed that among patients with SARS-CoV2 infection, the risk of both thromboembolic and hemorrhagic complications to which AF patients are particularly vulnerable is at least comparable to that of patients with pulmonary infection caused by other pathogens (bacterial or viral) ( 51 , 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important emphasizing that there are some pathophysiological explanations indicating that patients who develop AF de novo during pneumonia have increased risk of bleeding events (depletion of coagulation factors and platelets as a result of inflammatory response during infection) ( 53 ). Based on the available data, it can be conservatively assumed that among patients with SARS-CoV2 infection, the risk of both thromboembolic and hemorrhagic complications to which AF patients are particularly vulnerable is at least comparable to that of patients with pulmonary infection caused by other pathogens (bacterial or viral) ( 51 , 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important emphasizing that there are some pathophysiological explanations indicating that patients who develop AF de novo during pneumonia have increased risk of bleeding events (depletion of coagulation factors and platelets as a result of inflammatory response during infection) ( 53 ). Based on the available data, it can be conservatively assumed that among patients with SARS-CoV2 infection, the risk of both thromboembolic and hemorrhagic complications to which AF patients are particularly vulnerable is at least comparable to that of patients with pulmonary infection caused by other pathogens (bacterial or viral) ( 51 , 53 , 54 ). Considering the rationale presented above, it is worth emphasizing that the association between AF and pneumonia is not limited only to the COVID-19 pandemic, and the results we obtained may provide a point of consideration for patients with community acquired pneumonia caused by other causes than SARS-CoV2 virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…First, SARS-CoV2 interacts with the angiotensin converting enzyme (ACE)-2 receptor on endothelial cells, which results in an increased release of the vasoconstrictor angiotensin-II and an endothelial dysfunction [ 158 ]. In addition, inflammatory response plays a primary role through complement activation, elevating levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and IL-17A, which activate platelets, tissue factor and then the coagulation cascade [ 159 , 160 ]. Moreover, recent studies have shown alterations of both coagulation and fibrinolysis by multiple pathways, such as reduction of antithrombin and protein C and increasing of PAI-1 [ 160 , 161 ].…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%
“…In addition, inflammatory response plays a primary role through complement activation, elevating levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and IL-17A, which activate platelets, tissue factor and then the coagulation cascade [ 159 , 160 ]. Moreover, recent studies have shown alterations of both coagulation and fibrinolysis by multiple pathways, such as reduction of antithrombin and protein C and increasing of PAI-1 [ 160 , 161 ]. This hypercoagulation [ 162 ] and cytokine storm result in the alveolar thrombosis of SARS-CoV2 disease.…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%
“…Thromboembolic events are common and significantly contribute to the increased morbidity and mortality of COVID-19 patients. There are several inflammatory and prothrombotic mechanisms considered to be responsible for thrombosis in COVID-19, such as endothelial dysfunction, exaggerated inflammatory response that induces “cytokine storm”, and hypercoagulable state [ 3 , 4 ]. Since the onset of the COVID-19 pandemic, a considerable percentage of infected patients had documented thrombotic complications, including acute ischemic stroke (AIS).…”
Section: Introductionmentioning
confidence: 99%